Dano existencial e o direito à desconexão em face da intensificação do trabalho pela tecnologia - Pinheiro, Maria Tereza Nascimento Maruyama (2020)
It is noticeable that in recent years technology has been present in the daily lives of all human beings, gaining an increasing and bigger space in working relationships, optimizing time and productivity in the most different areas, allowing a more instantaneous communication, and also allowing internet connection to be constant in the life of an individual, who in most cases uses it uninterruptedly. If, on one hand, technology translates into great improvements and benefits to the person, on the other hand, it allows the employer to be constantly connected to his employees, guiding, supervising and even assigning tasks beyond working hours, resulting in a work intensification, once from anywhere, and at any given time it is possible to use technology to perform the many different tasks. It is understood that this intensification of work by technology, has resulted in a non-disconnection from work, depriving the individual from fully enjoying his free time, as well as the right to rest and leisure. Considering that rest is a human being need, and that it is through it that leisure can be enjoyed, and understanding it as a factor of personal and social development, preventing the employee from fully enjoying these rights, may well cause an existential damage to the employee, frustrating his life projects that are not related to his professional life, and even preventing investment in social, affective and family relationships. In view of this new reality, the present research seeks to understand whether the intensification of work by technology has resulted in existential damage to the worker. In order to achieve the desired understanding, bibliographic research will be carried out aiming at the essential categories to this understanding, namely, the dignity of the human being, the right to leisure and rest, intensification of work, disconnection from work, the right to disconnect, existential damage, and how the labor judiciary in Brazil has positioned itself against existential damage and the right to disconnect. The bibliographic research will be carried out by means of a bibliographic survey of the main works on the theme, among which the authors Lafargue (1880), Sarlet (2010), Dal Rosso (2008), Tuma (2016), Melo and Rodrigues (2018), Fidalgo, Oliveira and Fidalgo (2009), Oliveira Neto (2015), Souto Maior (2003), Lora (2013) and Soares (2012, 2017) stand out. It will also use documentary research using Brazilian legislation and international treaties on the subject, as well as analysis of legal documents, particularly the relevant jurisprudence on the topic matter of this research.